Research on Forest Carbon Sequestration Based on FSC Model and DeepAR Algorithm - Xu, Yin-di (Journal of Mathematics, 2022)
Forestry resources play an irreplaceable role in solving the problem of climate change. Forest managers to find a balance between carbon sinks and forest products, decisions must therefore take into account many aspects of forest value. This paper clarifies that forest carbon sequestration is mainly influenced by three aspects: human, climate, and nonclimatic physical factors, constructs a model for estimating the carbon sequestration rate of forest ecosystems based on forest age and the logistic growth equation, and combines human behaviour and climate influencing factors to make comprehensive corrections to the carbon sequestration rate of forest ecosystems per unit area. A model for calculating the carbon sequestration rate over time in a forest system was developed, which combined with the DeepAR Algorithm to obtain carbon sequestration. Then, this paper then assesses the various values of the forest, dividing the 25 factors affecting forest value assessment into five indices to establish a model of the forest ecosystem value assessment system for application to forest value assessment under different conditions. After determining the index system, we use the EWM-CVM to integrate the indexes into the value index based on the forest ecosystem to propose a management plan. And the PSO-BP algorithm is used to determine the transition point for forest management in order to optimise the ecological value of the forest.